Melihat resiliensi karyawan dari kecerdasan emosi dan efikasi diri - Tiana, Ade Amelia Siska; Rini, Rr Amanda Pasca; Lestari, Bawinda Sri (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
Resilience is an individual's ability to bounce back after experiencing stress or difficult situations in the work environment. Emotional intelligence and self-efficacy are thought to play a significant role in shaping this psychological resilience. This study aims to determine the relationship between emotional intelligence and self-efficacy with employee resilience. This study used a quantitative approach with a correlational method. The subjects in this study were employees working at PT Kharisma SF Sidoarjo. The sampling technique used was simple random sampling with a population of 250 people. Referring to the Krejcie & Morgan table, 150 participants were obtained. The instruments used in this study included an emotional intelligence scale, a self-efficacy scale, and a resilience scale. Data analysis was performed using multiple linear regression analysis techniques. The results showed a highly significant positive relationship between emotional intelligence and self-efficacy with employee resilience. This finding demonstrates the importance of developing emotional intelligence and self-efficacy as supporting factors for psychological resilience in the workplace.